Kizzuwatna - Trameri, Andrea. (Leiden ; Boston)
xv, 620 sayfa
Keywords: “In Kizzuwatna, Andrea Trameri presents a history of the kingdom of Kizzuwatna, located in Cilicia (southern Anatolia), from its origins to the fall of the Hittite Empire. Encompassing both philological and archaeological evidence in the discussion, this book is the first comprehensive historical study of interdisciplinary scope dedicated to Kizzuwatna and the region of Cilicia in the second millennium BC. The book presents and re-analyses a diverse array of sources and data, providing an updated overview of various topics of interest beyond political history - including historical geography, culture and religion, population and language. Some new findings and proposals further contribute to an improved understanding of the history of the Hittite kingdom and other neighboring regions in the Middle and Late Bronze Age (ca. 2000-1200 BC)“ --